2007
DOI: 10.1124/dmd.107.014845
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in mRNA Expression of ATP-Binding Cassette Efflux and Bile Acid Transporters in Kidney, Liver, and Intestine of 5/6 Nephrectomized Rats

Abstract: ABSTRACT:ATP-binding cassette (ABC) transporters including multidrug resistance proteins (Mdr), multidrug resistance-associated proteins (Mrp), and breast cancer resistance protein (Bcrp/Abcg2) play major roles in tissue defense. Abcg5/g8 is essential in cholesterol efflux. The present study was aimed at elucidating alteration in expression of these transporters and bile-acid transporters during chronic kidney disease (CKD) and underlying molecular mechanisms. Seven weeks after 5/6 nephrectomy (Nx), mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 57 publications
7
50
0
Order By: Relevance
“…This was confirmed for P-gp in rat livers, but not in kidneys, and after testosterone treatment P-gp levels in females reduced to male rat liver levels (40). The same study showed a similar effect on Mrp2 in rat livers, whereas Abcc2 gene expression levels were comparable in female and male kidney (39). For Mrp4, female predominant appearance is observed in murine kidney and liver (41).…”
Section: Steroid Hormonessupporting
confidence: 68%
See 1 more Smart Citation
“…This was confirmed for P-gp in rat livers, but not in kidneys, and after testosterone treatment P-gp levels in females reduced to male rat liver levels (40). The same study showed a similar effect on Mrp2 in rat livers, whereas Abcc2 gene expression levels were comparable in female and male kidney (39). For Mrp4, female predominant appearance is observed in murine kidney and liver (41).…”
Section: Steroid Hormonessupporting
confidence: 68%
“…Abcb1b, but not Abcb1a, gene expression is somewhat higher in females than in male mice kidneys (39). This was confirmed for P-gp in rat livers, but not in kidneys, and after testosterone treatment P-gp levels in females reduced to male rat liver levels (40).…”
Section: Steroid Hormonessupporting
confidence: 61%
“…In this work, canine ABCC1 expression correlated with that in human, with lower levels in the liver than in the intestine (Bleasby et al, 2006); however, in contrast to the other studied genes, the mRNA levels increased toward the large intestine (2.4-fold higher in the colon than in the jejunum). A similar gene expression trend along the gut was also observed in rats (Lu and Klaassen, 2008).…”
Section: Gapdh-normalized Mrna Levels In the Liversupporting
confidence: 61%
“…These results are consistent with a previous study reporting gender differences in abcc2/mrp2 mRNA and protein expression in a mouse model for chronic kidney disease. 49 Abcc2/mrp2, abcc3/mrp3 and abcc4/mrp4 expression in mice were also reported to be induced in the context of oxidative stress. 50 Mild chronic oxidative stress might be involved in PXE manifestation.…”
Section: Discussionmentioning
confidence: 99%